2018
DOI: 10.1080/21691401.2018.1426593
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of a nanofibrous silk tube as nerve guide for sciatic nerve regeneration

Abstract: A nanofibrous silk nerve conduit has been evaluated for its efficiency based on the promotion of peripheral nerve regeneration in rats. The designed tubes with or without Schwann cells were implanted into a 10 mm gap in the sciatic nerves of the rats. Four months after the surgery, the regenerated nerves were monitored and evaluated by macroscopic assessments and histology. The results demonstrated that the nanofibrous grafts, especially in the presence of Schwann cells, enabled reconstruction of the rat sciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The study reports successful results for bridging a 10 mm gap within the sciatic nerve [55]. The conceptual framework of this study was confirmed in a more recent study, and similar positive incomes were observed [99]. In line with these results, Gu et al assessed the ability of SF fibers with chitosan for providing a neuronal-like niche for culturing Schwann cells that were able to deposit ECM in the porosity of the biomaterial [152,153].…”
Section: The Importance Of Silk In Peripheral Nerve Injurysupporting
confidence: 75%
See 1 more Smart Citation
“…The study reports successful results for bridging a 10 mm gap within the sciatic nerve [55]. The conceptual framework of this study was confirmed in a more recent study, and similar positive incomes were observed [99]. In line with these results, Gu et al assessed the ability of SF fibers with chitosan for providing a neuronal-like niche for culturing Schwann cells that were able to deposit ECM in the porosity of the biomaterial [152,153].…”
Section: The Importance Of Silk In Peripheral Nerve Injurysupporting
confidence: 75%
“…SF fibers can be gathered in various collectors to make 2D and 3D highly arranged mats or weaves of different shapes. This method has the potential to fabricate highly arranged structures to guide cells and push them toward further proliferation, differentiation, and adhesion and to be used as conduits for axonal guidance and neuronal regeneration [44,99,100]. A main issue is the hardship of constructing structured 3D scaffolds to fill spatial defects in the nervous tissue [101].…”
Section: Fabrication Of Fiber-based Biomaterialsmentioning
confidence: 99%
“…Rehydration was performed with 100 to 70% graded alcohol, and the organic solution was removed by rinsing in ddH 2 O. Hematoxylin and eosin (HE) staining (Sigma-Aldrich), toluidine blue staining (Sigma-Aldrich) (Ebrahimi et al, 2018), myelin basic protein (MBP) immunostaining (Merolli et al, 2019) and iron staining (Sigma-Aldrich) (Liu and Ho, 2017) were used to stain the sections, with the results being examined by a light microscope AX80 (Olympus, Tokyo, Japan). Photographs of the toluidine blue staining sections taken under light microscopy at a 400 × magnification were used for quantification.…”
Section: Histological Stain and Myelinated Fiber Quantificationmentioning
confidence: 99%
“…NGCs are advantageous in that they reduce the ingrowth of scar tissue in the site of injury; contribute to the sprouting of axons from the proximal nerve; centralize growth factors secreted by the damaged nerve ends [37]. Currently, researchers have widely used natural or synthetic biomaterials to fabricate NGCs with various structural and physicochemical features ( Figure 2C-J) [38][39][40]. Tailoring NGC chemical structure and composition provide a possibility to obtain a conduit with desired properties such as excellent mechanical strength, good biocompatibility, biodegradability, and permeability.…”
Section: Nerve Tissue Engineering Strategiesmentioning
confidence: 99%